The Relevance of The Notarial Deed To The Deed of The Treatise of The Auction Made by The Notary As Class Ii Auction Officials - Nezsa Agyu Permata (Notary Master Programe, Faculty of Law Universitas Jenderal Soedirman, 2020)
The minutes of auction are the minutes of the auction made by the Bidding Officer which is an authentic. Deed and has perferct legal force (Explanation of Article 1 number 35 of the Minister of Finance Regulation Number 27/PMK.06/2016 concerning Bidding Immplementation Guidelines). Based on Article 15 paragraph (2) letter g of Law number 2 of 2014 concerning Position of Notary. It is explained that making the minutes of auction treaty is one of the Notary’s authorities. This means it cant be interpreted that the Auction Officer to make minutes of aution treaty. But in the implementation of the drafting of the minutes of auction there are 2 (two) ruless governing, namely the Notary, while the Auction Officer uses the Vendu Reglement reference, Stbl 1908:289, and in fact not all the Notary can make the auction treatise deed in accordance with the contents of the article, so that question artise regarding the auction treatise deed and the authentic deed make by the Notary the main issue raised in this study is how is the implementation of the authority of the Notary Public as a Class II Auction Officer in conducting the auction? And how is the relevance of the minute of the auction treaty with the Notary Public as Class II Auction Officer? Based on the result of research and conclusions that the Notary who made the auction treatise deed is the Notary in his capacity as a Class II Auction Officer who has followed the appointment process as a Class II Auction Officer, so that for the minutes of the auction tretise produced by a Notary Public in this case as a Class II Auction Officer, likened to authentic deeds as authetic deeds make by a Notaries. In the case of the making of the minutes of the auction treaty, a Notary who serves as a Class II Auction Officer needs to strongly apply the precautionary principle in making the minutes of the aution treaty, because the existing rules do not accommodate the possition of a Notary who serves as a Class II Auction Officer. Keywords: Deed of Minutes of Auction, Notary Public, Class II Auction Officer.